Fostering Interfaith Dialogue through Formation: Insights from Pope Francis' Evangelii Gaudium - Jehaut, Rikardus Moses; Julivadistanto, Thomas (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2023)
This study investigates the role of formation in interreligious dialogue, particularly between Catholics and Muslims, guided by Pope Francis' perspectives in Evangelii Gaudium. The research employs a qualitative approach, conducting a content analysis of the Evangelii Gaudium document and supplementary secondary literature to explore the implications of formation in religious interactions. The study identifies formation as a critical tool for enhancing dialogue, underscoring its necessity for fostering a deeper understanding and mutual respect among religious communities. It highlights the integration of daily life interactions and structured faith formation programmes as vital for practising the theological insights in real-world settings.This research contributes a methodological framework for assessing the practical impacts of religious teachings on interfaith dialogue and suggests ways to improve these interactions through targeted educational efforts. The findings advocate for ongoing dialogue initiatives that are informed by robust formation processes to sustain peaceful coexistence in diverse societies.Â